2021
DOI: 10.3390/proteomes9020026
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of Semispecific Peptide Search Parameter Enables Identification of Previously Undescribed N-Terminal Peptides and Conserved Proteolytic Processing in Cancer Cell Lines

Abstract: Liquid chromatography-tandem mass spectrometry (LC-MS/MS) has become the most commonly used technique in explorative proteomic research. A variety of open-source tools for peptide-spectrum matching have become available. Most analyses of explorative MS data are performed using conventional settings, such as fully specific enzymatic constraints. Here we evaluated the impact of the fragment mass tolerance in combination with the enzymatic constraints on the performance of three search engines. Three open-source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Semi‐specific peptide searches facilitate the detection of endogenous proteolytic activity, often evident in protein degradation processes. Such activity leads to protein cleavage, producing truncated versions with terminal amino acids that may differ from the specificity of the enzyme used during proteomic sample processing (Fahrner et al ., 2021). Surprisingly, LL cells accumulated significantly more cleaved peptides of many PSI and all LHCI subunits (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Semi‐specific peptide searches facilitate the detection of endogenous proteolytic activity, often evident in protein degradation processes. Such activity leads to protein cleavage, producing truncated versions with terminal amino acids that may differ from the specificity of the enzyme used during proteomic sample processing (Fahrner et al ., 2021). Surprisingly, LL cells accumulated significantly more cleaved peptides of many PSI and all LHCI subunits (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that semi-tryptic (re-)analysis of proteomic data might yield novel insight into endogenous proteolytic processing prior to sample harvesting and eventual trypsination [61] , [62] , [63] . Naturally, this re-analysis can only shed light on non-tryptic, endogenous proteolytic processing.…”
Section: Resultsmentioning
confidence: 99%
“…Semi-specific peptide searches facilitate the detection of endogenous proteolytic activity, often evident in protein degradation processes. Such activity leads to protein cleavage, producing truncated versions with terminal amino acids that may differ from the specificity of the enzyme used during proteomic sample processing (Fahrner et al ., 2021). In our search for semi-tryptic-cleaved peptides in the PSI of both LL and HL cells as potential indicators of protein degradation, we observed no increase in peptide cleavage for psaD or any other PSI subunit at HL cells (Table S6).…”
Section: Resultsmentioning
confidence: 99%